MARC Formats in China: Local or International? - Gu, Ben (JLIS.it, 2013)
The application of MARC formats in Chinese libraries has a history of about 20 years. At the age of internationalization and digitization, people ask the question: why we chose UNIMARC for the basis of CNMARC? Is it the best choice for China? Are there any other options? In this paper, the author reviews many historical documents and analyzes the present status of MARC formats in China.